Prognostic value of baseline metabolic tumor volume in children and adolescents with intermediate‐risk Hodgkin lymphoma treated with chemo‐radiation therapy: FDG‐PET parameter analysis in a subgroup from COG AHOD0031. Issue 9 (10th July 2021) - Milgrom, Sarah A.; Kim, Jihyun; Chirindel, Alin; Kim, Jongho; Pei, Qinglin; Chen, Lu; Buxton, Allen; Kessel, Sandy; Leal, Jeffrey; McCarten, Kathleen M.; Hoppe, Bradford S.; Wolden, Suzanne L.; et al.
Abstract: Background: Positron emission tomography (PET)‐based measures of baseline total‐body tumor burden may improve risk stratification in intermediate‐risk Hodgkin lymphoma (HL). Materials and methods: Evaluable patients were identified from a cohort treated homogeneously with the same combined modality regimen on the Children's Oncology Group AHOD0031 study. Eligible patients had high‐quality baseline PET scans. Metabolic tumor volume (MTV) and total lesion glycolysis (TLG) were each measured based on 15 thresholds for every patient. Univariate and multivariable Cox regression and Kaplan–Meier survival analyses assessed for an association of MTV and TLG with event‐free survival (EFS). Results: From the AHOD0031 cohort ( n = 1712), 86 patients were identified who (i) were treated with four cycles of doxorubicin, bleomycin, vincristine, etoposide, prednisone, cyclophosphamide (ABVE‐PC) chemotherapy followed by involved field radiotherapy, and (ii) had a baseline PET scan that was amenable to quantitative analysis. Based on univariate Cox regression analysis, six PET‐derived parameters were significantly associated with EFS. For each of these, Kaplan–Meier analyses and the log‐rank test were used to compare patients with highest tumor burden (i.e., highest 15%) to the remainder of the cohort. EFS was significantly associated with all six PET parameters (all p < .029). In a multivariable model controlling for important covariates including disease bulk and response to chemotherapy, MTV2BP was significantly associated with EFS ( p = .012). Conclusion: Multiple baseline PET‐derived volumetric parameters were associated with EFS. MTV2BP was highly associated with EFS when controlling for disease bulk and response to chemotherapy. Incorporation of baseline MTV into risk‐based treatment algorithms may improve outcomes in intermediate‐risk HL.